Five ballades for the house of Foix - Lefferts, Peter; Huot, Sylvia (Antico edition, 1988)
Four of these ballades (Phiton Phiton, Le mont Aon, Se Galaas and Se July Cesar) honour Gaston Febus, the hero of the motets in AE23. The other piece Se Alixandre praises Gastons nephew and successor Mathieu de Foix. Se Galaas and Se July Cesar are in the rhythmically complex mannered style fashionable in the later fourteenth century. Probably intended for entirely vocal performance, these works also sound well on instruments. ix + 22 pages.